SPECIFIC FEATURES OF ENHANCING READING COMPETENCE AMONG PHILOLOGY STUDENTS - Saidov Ravshan Tursunovich (Modern American Journals, 2025)
This article examines the specific features of developing and enhancing reading competence among philology students. It emphasizes the role of literary and academic texts, critical thinking, metacognitive awareness, and reading strategies in shaping students’ intellectual and professional skills. The paper explores cognitive processes involved in reading, the importance of linguistic and intertextual analysis, and the pedagogical-psychological characteristics necessary for effective reading instruction. Furthermore, it highlights the integration of technology, multimodal resources, and literature in language classrooms. The findings suggest that a combination of literary and academic materials, supported by appropriate pedagogical approaches, significantly contributes to the development of philology students’ reading competence.
Keywords: Reading competence, philology students, literary texts, academic texts, critical thinking, metacognitive approach, reading strategies